2016
DOI: 10.1216/jie-2016-28-1-91
|View full text |Cite
|
Sign up to set email alerts
|

The direct scattering problem of obliquely incident electromagnetic waves by a penetrable homogeneous cylinder

Abstract: In this paper we consider the direct scattering problem of obliquely incident time-harmonic electromagnetic plane waves by an infinitely long dielectric cylinder. We assume that the cylinder and the outer medium are homogeneous and isotropic. From the symmetry of the problem, Maxwell's equations are reduced to a system of two 2D Helmholtz equations in the cylinder and two Helmholtz equations in the exterior domain coupled on the boundary. We prove uniqueness and existence of this differential system by formula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The scatterer is illuminated by a time-harmonic transverse magnetic polarized electromagnetic plane wave, the so-called oblique incident wave. The cylindrical symmetry and the homogeneity of the medium reduces the three-dimensional scattering problem (1) -(3) to a two-dimensional problem only for the z−components of the fields, see for instance [11,21,26].…”
Section: Formulation Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The scatterer is illuminated by a time-harmonic transverse magnetic polarized electromagnetic plane wave, the so-called oblique incident wave. The cylindrical symmetry and the homogeneity of the medium reduces the three-dimensional scattering problem (1) -(3) to a two-dimensional problem only for the z−components of the fields, see for instance [11,21,26].…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…For the convergence and error analysis, see [16]. We do not present here the parametrized forms of the integral operators (16) since they can be found in many works, we refer the reader to the books [8,17] and to [11,Section 4] for a complete list of all forms and special decompositions.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In article [5], the author used the double Fourier transform for the inverse problem solution. Furthermore, there are some other analytical and numerical works related to this topic [6][7][8][9][10][11][12][13][14]. There are also other authors who used the Method of Auxiliary Sources to solve direct scattering problem [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The transmission conditions now contain also the tangential derivatives of the electric and magnetic fields. In [10] we showed that the corresponding direct problem is well-posed and we constructed a unique solution using the direct integral equation method. A similar problem has been considered for an impedance cylinder embedded in a homogeneous [24], and in an inhomogeneous medium [22].…”
Section: Introductionmentioning
confidence: 99%